Pengaruh Promosi, Label Halal Dan Varian Produk Terhadap Keputusan Pembelian Produk Perawatan Rambut Natur Dengan Brand Image Sebagai Variabel Intervening Pada Masyarakat Muslim Kota Medan - Fenny Ade Annisah; Nurbaiti Nurbaiti; Muhammad Ikhsan Harahap (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
The background of this research aims to determine and analyze the influence of the marketing mix, which includes promotional variables, halal labels and product variants on purchasing decisions for a product through brand image in the Medan Muslim community. The research approach taken was to use a quantitative-descriptive approach using the path analysis method. Path analysis is an extension of the use of regression analysis which aims to estimate the direct or indirect influence of the variables hypothesized in the research. Based on the test results, it can be concluded that promotions, halal labels and product variants have a significant effect on product brand image. It was also found that there was a significant influence between promotions, product variants and brand image on purchasing decisions, while the halal label did not have a significant influence on purchasing decisions for Natur products in the Muslim community of Medan. It is hoped that Natur can maintain and improve the promotional strategies carried out by holding various activities to portray a positive brand attitude towards consumers, because this greatly influences purchasing decisions.